1972
DOI: 10.1021/jo00979a023
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of isoprenoids. XVII. Cycloaddition reactions of norbornadiene with some unsymmetrically substituted dienophiles. Competitive ionic additions with homo-Diels-Alder reactions

Abstract: The saturated acid 18 was esterified in methanol by the same procedure used for the preparation of the ester 17. The product 19 was obtained in 89% yield as a colorless oil: bp 126-127°; ir (neat) 1750 cm"1 (C=0); nmr (CDC13) 3.68 (s, 3, OCH3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Comparison of the above results with the cycloaddition reactions of Q or NBD with organic unsaturated compounds is of interest in view of the elucidation of the characteristic features of rhodiadithiolene: Sasaki et al [14] reported that the reaction of NBD with chlorocyanoacetylene affords the ½2 þ 2 cycloadduct (4) and its skeletal rearrangement product (5) via an ionic intermediate (6), together with homo-Diels-Alder adduct (3) (Scheme 3). Thus, the formation of compound 5 suggests that an ionic cycloaddition initiated by an exo approach of chlorocyanoacetylene to NBD is competing with the homo-Diels-Alder reaction.…”
Section: Mechanism Of Adduct Formationmentioning
confidence: 98%
“…Comparison of the above results with the cycloaddition reactions of Q or NBD with organic unsaturated compounds is of interest in view of the elucidation of the characteristic features of rhodiadithiolene: Sasaki et al [14] reported that the reaction of NBD with chlorocyanoacetylene affords the ½2 þ 2 cycloadduct (4) and its skeletal rearrangement product (5) via an ionic intermediate (6), together with homo-Diels-Alder adduct (3) (Scheme 3). Thus, the formation of compound 5 suggests that an ionic cycloaddition initiated by an exo approach of chlorocyanoacetylene to NBD is competing with the homo-Diels-Alder reaction.…”
Section: Mechanism Of Adduct Formationmentioning
confidence: 98%
“…Other examples of acetylenes include chlorocyanoacetylene (79, no experimental details) [57] and phenyl(ptolylsulphonyl)acetylene (8 0 , 15 d, 20 o C) [58,59] giving in reaction with Q cycloadducts 8 1 and 8 2 , respectively.…”
Section: P-benzoquinonementioning
confidence: 99%
“…The reactivity of 3,3-dimethyl-l,4-pentadiene (3) in the homo-Diels-Alder reaction was examined with a variety of dienophiles. Although the addition of TONE to a benzene solution of 3 produces a light amber color, heating of this solution, even at 145 °C for 52 h, does not lead to any detectable reaction.…”
Section: Scheme Imentioning
confidence: 99%
“…Since the ease of the reaction must depend critically on the alignment and distance between the double bonds, we have investigated the behavior in this reaction of several dienes in which the double bonds are at increasingly greater distances than in norbornadiene. The dienes studied were bicyclo[2.2.2]octa-2,5-diene (1), bicyclo[3.2.2]nona-6,8-diene (2), and 3,3-dimethvl-1,4-pentadiene (3). The results of these 3 studies along with previous information in the literature can be used to assess the scope of the homo-Diels-Alder reaction.…”
mentioning
confidence: 99%